Analisis Gaya Kepemimpinan Kepala Sekolah sebagai Sistem Kontrol dan Pengaruhnya terhadap Kinerja Guru dan Tenaga Kependidikan pada SDN 1 Dompu - Fena Febrianti; Irwansyah Irwansyah; Shoalihin Shoalihin (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to analyze the influence of the principal's leadership style on the performance of teachers and educational staff at SDN 1 Dompu. This study uses a quantitative approach with explanatory research and a causal-comparative method. The sample was taken saturately, involving all 48 teachers and educational staff, with 40 questionnaires suitable for analysis. Primary data were collected through the distribution of questionnaires and analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through SmartPLS 4.0. The results of the study indicate that the principal's leadership style has a positive effect on the performance of teachers and educational staff. Principals who combine authoritarian and democratic styles in a balanced manner are able to create a disciplined, participatory, and productive work environment. This study suggests the need to develop principals' leadership competencies to improve educational quality and recommends further studies with a broader scope to strengthen the generalization of the findings.